Anti-impact performance of bionic tortoiseshell-like composites. (1st January 2023) - Wang, Ji; Hu, Dayong; Zhang, Zhiqiang; Pei, Baoqing; Xu, Rongkai; Wu, Xueqing
Highlights: A bionic tortoiseshell-like composites was designed and manufactured by 3D printing technology. The drop tower impact experiments were conducted to test the impact resistance of composites plates, and bionic tortoiseshell-like composites showed the best impact resistance. The influence of ply angle changes and dimension on the impact resistance was investigated by drop tower experiments. The crack propagation mode in the suture structure of the Bio-T composite plates is examined to gain the underlying mechanisms during impact. Abstract: Biological stiff-soft phase composite structures, such as tortoise shells and conch shells, have excellent anti-impact performance to withstand various types of high-stress events encountered in nature. A remarkable 3D interdigitating zigzag architecture in the tortoise shell, named occlusal suture structure, makes the tortoise shell simultaneously possess high mechanical strength and toughness, which is also an ideal stiff-soft phase composite prototype to mimic. In this study, four types of bionic anti-impact composite plates that feature the hard-soft phase architecture of tortoiseshell (Bio-T), mollusk shell (Bio-M), beetle exoskeleton (Bio-B) and nacre (Bio-N) and a homogeneous structure plate (HSP) are designed, to systematically examine and compare their roles in impact energy dissipation. Through an integrated approach combining additive manufacturing and drop tower testing, the peak force, residual velocity, and energy absorption of these bionic composite plates are studied and compared. Experimental results indicate that the Bio-T composite plate has the best impact resistance, compared with the other three bionic composites. Furthermore, the influence of the ply angle and the dimension of suture structure on the impact resistance of the Bio-T composite plate is identified. The [0°/30°/0°] arrangement is able to resist higher loads before failure. The 3D Bio-T composite plate provides a significant enhancement of anti-impact performance than the 2D Bio-T composite plate. Finally, the crack propagation mode in the suture structure of the Bio-T composite plates is examined, enhancing our understanding of the underlying mechanisms during impact. Such findings may prove useful for the design of future protective apparatus for soldiers and aircrafts, with improved anti-impact performance.